Cognition, functionality and depression indicative among elderly - Winnie Andaki Nunes; Flavia Aparecida Dias; Janaína Santos Nascimento; Nayara Cândida Gomes; Darlene Mara dos Santos Tavares (Rev Rene)
Objective: to describe the socioeconomic characteristics of the elderly according to cognitive status, and, to associate the cognitive decline with functional disability and depression indicative among the elderly. Methods: this is a quantitative, retrospective and observational study with 92 elderly. The used instruments were: Mini Examination of Mental State; Katz Index; Lawton and Brody Scale and Abbreviated Geriatric Depression Scale. Statistical analysis and chi-square test (p<0.05) were used. Results: elderly with a cognitive decline for females were predominant, 80 years and older, widowed and living with children, with one to three years of study, individual income up to a minimum wage. The proportion of elderly with a dependent cognitive decline in basic activities of daily living (p=0.043) and instrumental activities of daily living (p=0.008) was higher than independent. There were no significant differences in the depression indicative (p=0.437). Conclusion: the proportion of dependent elderly was higher in those with cognitive decline.